Gauging the gravity of the situation: The use and abuse of expertise in estimating the economic costs of Brexit - Christoph Semken; Colin Hay (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2021)
HM Treasury's estimation of the economic consequences of Brexit - using standard macroeconomic models - during the EU referendum campaign represents a remarkable intervention in a highly politicized public debate. It raises a series of questions about the use of economic expertise. Through a detailed theoretical and empirical critique of the Treasury's methodology - and a reassessment of the likely effects of Brexit in light of this - we cast doubt on the utility of their approach, highlighting methodological issues, unrealistic assumptions, and misrepresentations of established facts. In the process we seek to identify some of the wider implications for the use and potential abuse of economic expertise in highly charged political contexts, such as the EU referendum debate.
Keywords: 330; Brexit; DSGE model; economic consequences; economic expertise; gravity model; HM Treasury; methodology